2018
DOI: 10.1055/a-0808-3186
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic grading of gastric intestinal metaplasia (EGGIM): a multicenter validation study

Abstract: Background Random biopsies are recommended to identify individuals at risk of gastric adenocarcinoma. Cumulative evidence suggests that narrow-band imaging (NBI) can be used to grade gastric intestinal metaplasia (GIM). We aimed to externally validate a classification of endoscopic grading of gastric intestinal metaplasia (EGGIM). Methods Consecutive patients in two centers were submitted to high resolution white-light gastroscopy followed by NBI to estimate EGGIM – a score (0 – 10) resulting from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 20 publications
6
94
0
Order By: Relevance
“…Villous appearance, whitish mucosa, and rough mucosal surface are helpful indicators for the endoscopic diagnosis of intestinal metaplasia. 32,33 Intestinal metaplasia score of 0 was defined as the absence of intestinal metaplasia, 1 as the presence of intestinal metaplasia within the antrum, and 2 as intestinal metaplasia extending into the corpus. Intestinal metaplasia score is calculated based on the diagnosis established using white-light imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Villous appearance, whitish mucosa, and rough mucosal surface are helpful indicators for the endoscopic diagnosis of intestinal metaplasia. 32,33 Intestinal metaplasia score of 0 was defined as the absence of intestinal metaplasia, 1 as the presence of intestinal metaplasia within the antrum, and 2 as intestinal metaplasia extending into the corpus. Intestinal metaplasia score is calculated based on the diagnosis established using white-light imaging.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that in the absence of a typical pattern of IM by NBI, the predictive negative value for extensive IM is excellent independent of prevalence of IM [3,5]. In this context, we believe that random biopsies to confirm absence of preneoplastic conditions could be spared unless testing for Hp status is indicated.…”
Section: Normal With Wle Absent Im With Virtual Ce (Eggim 0)mentioning
confidence: 86%
“…For diagnosis (patient not previously known to have IM), NBItargeted biopsies should be taken in separate vials from each location (antrum/incisura and corpus) to identify individuals at high risk. The exception could be in countries with IM prevalence > 25 %, where EGGIM positive predictive value for extensive IM is ≥ 85 % and, therefore, in theory biopsies could be avoided [5]. However, in our opinion, in most diagnostic cases, biopsies from the more representative areas in the antrum and in the corpus should be taken in separate vials to also confirm the histological diagnosis.…”
Section: Extensive Im (Eggim 5 -10)mentioning
confidence: 91%
See 2 more Smart Citations